Feed back fuzzy state space modeling for solving inverse problems in a multivariable dynamical system [electronic resource] - Izaz Ullah Khan, 1982-; Tahir Ahmad, supervisor; Normah Maan; Fakulti Sains (2013)
Thesis (Ph.D (Matematik)) - Universiti Teknologi Malaysia, 2013